The Development of the Slovak Agricultural Landscape in a Changing World - Izakovičová, Zita; Špulerová, Jana; Raniak, Andrej (Frontiers in Sustainable Food Systems, 2022)
The agricultural landscape as a space for food production and habitat for all living organisms is under constant pressure to use its plots and is accompanied by constant changes. Various socio-economic, technical or political drivers have caused land use changes, which are linked to a number of socio-economic and environmental problems, e.g. conflicts in various land uses, changes of landscape character, increasing anthropisation of the territory and disturbing spatial ecological stability, threatening the quality of environment and overexploitation of natural resources. The aim of the paper is to evaluate land use changes in the Slovak republic over the last 100 years, to identify key periods of land-management practices and prevailing drivers, and to specify the socio-economic and environmental impacts of land-use change. We organized a workshop with guided brainstorming to identify individual eras of agricultural development and their impacts. In total, we identified five main periods of agricultural landscape development and specified the characteristic landscape structure. Knowledge of the basic drivers of land use change as well as knowledge of impacts is important to develop effective policies and to ensure effective protection of the values of a traditional agricultural landscape.